Active sites in Cu-SSZ-13 deNOx catalyst under reaction conditions: a XAS/XES perspective. (May 2016) - Lomachenko, Kirill A; Borfecchia, Elisa; Bordiga, Silvia; Soldatov, Alexander V; Beato, Pablo; Lamberti, Carlo
Abstract: Cu-SSZ-13 is a highly active catalyst for the NH3 -assisted selective catalytic reduction (SCR) of the harmful nitrogen oxides (NOx, x=1, 2). Since the catalytically active sites for this reaction are mainly represented by isolated Cu ions incorporated into the zeolitic framework, element-selective studies of Cu local environment are crucial to fully understand the enhanced catalytic properties of this material. Herein, we highlight the recent advances in the characterization of the most abundant Cu-sites in Cu-SSZ-13 upon different reaction-relevant conditions made employing XAS and XES spectroscopies, complemented by computational analysis. A concise review of the most relevant literature is also presented.